A leitura no livro didático de língua portuguesa: outras formas de dizer o mesmo - Leão, Rosaura Maria Albuquerque (2007)
The object of our research is the text books of Portuguese language used in the fundamental level of school, adopted by public schools in Brazil which are representatives of different decades covering approximately third years from the 70th decade till now. This linguistic materiality was chosen as the importance the didactic book assumed in teaching and learning process for the teachers as well as for the students. This thesis is supported in the theoretical Analyse du discours principles and the objective is to verify how the reading gesture discursivises the place of interpretation in these text books. From this perspective, there is no corpus ready to analyze and the linguistic marks are being looked for confronted with the materiality in a work of observation, description and interpretation. It was observed that almost totally of the activities of reading followed the content model and established a word by word relationship between thought/world/language in which the division between content and form is unrelated, taking the word in a ritual whose interpretation/comprehension is repetition of models in modeled activities with modeled answers making the reading a homogeneous activity. It is a model which opposed to the discursive parameters of reading in which the interpretation is meaning construction grasped by the subject/the learner through history. This model is found in very few of the didactic books analyzed. In fact, there is a kind of actualization of the activities proposed by other ways of saying the same.